Visitor Satisfaction Analysis of Library Services at Sultan Agung Islamic University Using Libqual and Fuzzy - Riansyah, Andi; Pratama, Nirmala Putri; Assegaf, Badieah (Jurusan Teknologi Informasi Universitas Semarang, 2020)
Quality of service is part of the services provided by the Universitas Islam Sultan Agung (UNISSULA) library so that it matches the expectations and needs of visitors. There is not yet a system that can be used to measure service quality so that the process of measuring services is less than optimal. So it needs to be made a system that can be used to evaluate the quality of library services. The system was built using two methods in its development, namely the Libqual Method and the Fuzzy Tsukamoto Method by using a Likert scale from values 1 to 5. The Libqual method is used to measure the gap between perception and expectations with two calculations namely Adequancy Gap (AG) and Superiority Gap (SG) , in Fuzzy Tsukamoto there are four process processes, namely fuzzyfication, rule formation, inference and defuzzyfication machines which are used as ranking of each question on the questionnaire regarding service quality. Ranking aims to find out the question items about the quality of service that has the best value on a scale from small to large. The results of calculations using Libqual and Fuzzy Tsukamoto from three dimensions that exist in Libqual, Library as Place gets first rank with a value of 3,31 which is the most optimal service quality.